FULSOME: a fuzzy logic modeling tool for software metricians - MacDonell, SG; Gray, AR; Calvert, JM (IEEE Computer Society Press, 1999)
There has been a growing body of literature suggesting that some of the problems faced by software development project managers can be at least partially overcome by using fuzzy logic techniques. However, one issue that has been generally overlooked in this recommendation is the means by which these “software metricians” can collect data for, develop, and interpret fuzzy logic models in practice. We describe a freely available system that has been built with this in mind called FULSOME (FUzzy Logic for SOftware MEtrics). While there are many tools available for developing fuzzy models, it is suggested that before there will be real adoption of such techniques by project managers there will need to be suitable tools that support their particular workflows and that use appropriate terminology. Another requirement will be the development of some standard procedures and definitions for such models. Issues involved with membership function elicitation and extraction are also discussed as a first step towards this second goal.
Keywords: Application software; Fuzzy logic; Information science; Monitoring; Predictive models; Programming; Project management; Software development management; Software metrics; Software tools